EFEK KONVERGENSI KERANGKA DASAR IFRS (IAS 12 REVISI) TERHADAP PSAK 46 - Ida Kristiana (Universitas Muhammadiyah Semarang, 2017)
This purpose of this study to examine the presence or absence of securities caused by the convergence of IFRS to Statement of Accounting Standards of Income Tax (PSAK 46), by simulating the financial statements of PT. Garuda Indonesia Airlines (GIA) and PT. Telkom Indonesia. This study also looks at the differences between financial reports that are not convergent compared with financial reportsthat are already convergent with IFRS This study used a comparison method between the statements presented in IFRS with the statements presented in PSAK 46. The unit of analysis in this study is the International Financial ReportingStandard (IFRS) and Statement of Financial Accounting Standards on income tax accounting as well as books and articles related to both. The results of this study indicate that the convergence of the IFRS framework to PSAK 46 has a significant impact on the financial statements, especially on capital budgeting, because the tax will affect the calculation of cash flow. Besides this convergence also has an impact on the tax calculation in the financialstatementsKeywords: IFRS, PSAK, Financial Statement, Convergence